Polar regions are critical in achieving global sustainable development goals - Xin Li; Huadong Guo; Guodong Cheng; Xiaoyu Song; Youhua Ran; Min Feng; Tao Che; Xinwu Li; Lei Wang; Anmin Duan; Donghui Shangguan; Deliang Chen; et al. (Nature Communications)
Abstract As important components of global commons, environmental changes in polar regions are crucial to the local and global sustainability. However, they have received little attention in the current framework of sustainable development goals (SDGs). This study examines the impacts of climate change in polar regions, emphasizing the interconnectedness of these areas with other parts of the global system. Here we show that polar regions are a limiting factor in achieving global SDGs, similar to the “shortest stave” in Liebig’s barrel, primarily due to the teleconnection effects of climate tipping elements. Proactive actions should ensure polar regions aren’t left behind in achieving global SDGs. We proposed a specific SDG target and five indicators for the interconnected effect of the cryosphere on climate actions and incorporate considerations for Indigenous peoples in polar regions. With the right actions and strengthened global partnerships, polar regions can be pivotal for advancing global sustainable development.